Glyphosate Induces Metaphase II Oocyte Deterioration and Embryo Damage by Zinc Depletion and Overproduction of Reactive Oxygen Species. (June 2020) - Yahfoufi, Zeina A.; Bai, David; Khan, Sana N.; Chatzicharalampous, Charalampos; Kohan-Ghadr, Hamid-Reza; Morris, Robert T.; Abu-Soud, Husam M.
Highlights: Glyphosate, a metal chelator, is the most popular herbicide in modern agriculture. Glyphosate exposure deteriorates oocyte quality through pericentrin disappearance. Glyphosate mediates zinc deficiency in oocytes and embryos. Glyphosate also enhances reactive oxygen species in both oocytes and embryos. Our data may benefit patients exposed to toxic doses of chelators. Abstract: Glyphosate is the most popular herbicide used in modern agriculture, and its use has been increasing substantially since its introduction. Accordingly, glyphosate exposure from food and water, the environment, and accidental and occupational venues has also increased. Recent studies have demonstrated a relationship between glyphosate exposure and a number of disorders such as cancer, immune and metabolic disorders, endocrine disruption, imbalance of intestinal flora, cardiovascular disease, and infertility; these results have given glyphosate a considerable amount of media and scientific attention. Notably, glyphosate is a powerful metal chelator, which could help explain some of its effects. Recently, our findings on 2, 3-dimercapto-1-propanesulfonic acid, another metal chelator, showed deterioration of oocyte quality. Here, to generalize, we investigated the effects of glyphosate (0 – 300 μM) on metaphase II mouse oocyte quality and embryo damage to obtain insight on its mechanisms of cellular action and the tolerance of oocytes and embryos towards this chemical. Our work shows for the first time that glyphosate exposure impairs metaphase II mouse oocyte quality via two mechanisms: 1) disruption of the microtubule organizing center and chromosomes such as anomalous pericentrin formation, spindle fiber destruction and disappearance, and defective chromosomal alignment and 2) substantial depletion of intracellular zinc bioavailability and enhancement of reactive oxygen species accumulation. Similar effects were found in embryos. These results may help clarify the effects of glyphosate exposure on female fertility and provide counseling and preventative steps for excessive glyphosate intake and resulting oxidative stress and reduced zinc bioavailability.